Supramolecular plasmonic magnetic gels for controlled drug delivery - Veloso, Sérgio Rafael Silva (2020)
In this work, two different magnetic/plasmonic nanoparticle architectures were developed, characterized and combined with a naproxen N-capped dehydropeptide-based hydrogel. Spectroscopic techniques and rheologic assays were used were used to assess the gel physicochemical properties, the incorporation of a model drug (curcumin), drug transport towards model membranes and controlled drug release.